2013
DOI: 10.1002/jts.21819
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Regulation Difficulties Mediate Associations Between Betrayal Trauma and Symptoms of Posttraumatic Stress, Depression, and Anxiety

Abstract: Emotion regulation difficulties following trauma exposure have received increasing attention among researchers and clinicians. Previous work highlights the role of emotion regulation difficulties in multiple forms of psychological distress and identifies emotion regulation capacities as especially compromised among survivors of betrayal trauma: physical, sexual, or emotional maltreatment perpetrated by someone to whom the victim is close, such as a parent or partner. It is unknown, however, whether links betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
70
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(85 citation statements)
references
References 76 publications
13
70
2
Order By: Relevance
“…Simultaneously, higher emotion dysregulation increased the risk of developing an SUD. These findings are in line with past investigations of emotion dysregulation as a mediator of the relationship between maltreatment and different aspects of psychopathology [28,29,40] . The findings are further in line with studies on individuals without traumatization, where aspects of emotion regulation were identified as resilience factors [41] .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Simultaneously, higher emotion dysregulation increased the risk of developing an SUD. These findings are in line with past investigations of emotion dysregulation as a mediator of the relationship between maltreatment and different aspects of psychopathology [28,29,40] . The findings are further in line with studies on individuals without traumatization, where aspects of emotion regulation were identified as resilience factors [41] .…”
Section: Discussionsupporting
confidence: 92%
“…This has been supported by a study in an SUD sample so far, where childhood emotional and physical abuse were associated with emotion dysregulation [21] , while other studies found that different aspects of emotion dysregulation, like impulse control difficulties, mediate childhood maltreatment and psychopathology [28,29] . However, there are limitations to these studies, including the common use of college samples instead of clinical or exclusively traumatized samples or the examination of only single subscales of emotion dysregulation.…”
Section: The Mediating Role Of Emotion Dysregulation and The Present mentioning
confidence: 74%
“…A study involving a sample of young adults found that emotional dysregulation mediated the association between high-betrayal trauma (i.e., abuse perpetrated by a close individual, as opposed to abuse perpetrated by a stranger or trauma that are not caused by another human being) and various mental health symptoms including anxiety, depression, intrusions, and avoidance (Goldsmith et al, 2013). Emotion regulation was also found to mediate the association between maltreatment and internalized and externalized behavior problems in school-age samples (Alink et al, 2009;Kim-Spoon et al, 2013).…”
Section: Mediational Analysis With Emotion Regulation and Dissociationmentioning
confidence: 99%
“…Avoidant strategies are related to higher levels of PTSD and depressive symptoms, whereas emotional expression is associated with fewer symptoms (Hassija, Luterek, Naragon-Gainey, Moore, and Simpson 2012). In addition, ineffective emotion regulation strategies may contribute to the relationship between betrayal trauma exposure and subsequent symptoms (Goldsmith, Chesney, Heath, and Barlow 2013).…”
Section: Discussionmentioning
confidence: 99%